2018
DOI: 10.1007/s00261-018-1642-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of magnetic resonance imaging in rectal cancer patients: Society of Abdominal Radiology (SAR) rectal cancer disease-focused panel (DFP) recommendations 2017

Abstract: These expert consensus recommendations can be used as guidelines for primary and post-treatment staging of rectal cancer using MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 81 publications
1
76
0
3
Order By: Relevance
“…Intravenous butilscopolamine is also administered routinely at our centre in the absence of contraindications, between scout and (oblique axial) T2-WI acquisitions, to minimise artefacts due to peristalsis. Neither the use of small enema nor the use of spasmolytic agents has reached consensus by SAR or ESGAR expert panels and is therefore considered optional according to their respective guidelines [13,73].…”
Section: Rectal Cancer Staging Templatesmentioning
confidence: 99%
“…Intravenous butilscopolamine is also administered routinely at our centre in the absence of contraindications, between scout and (oblique axial) T2-WI acquisitions, to minimise artefacts due to peristalsis. Neither the use of small enema nor the use of spasmolytic agents has reached consensus by SAR or ESGAR expert panels and is therefore considered optional according to their respective guidelines [13,73].…”
Section: Rectal Cancer Staging Templatesmentioning
confidence: 99%
“…As per Society of Abdominal Radiology Disease Focused Panel (SAR-DFP) recommendations and guidelines, rectal gel administration is not required for initial staging assessment. 21 Although rectal distension can provide a more accurate assessment of the tumor stalk in polypoid masses, some studies have found that distension can actually alter the distance between rectal wall and MRF, potentially skewing measurements for the margin of resection. 22 This is especially true in the lower rectum posteriorly where the fat plane between rectal wall and MRF is most susceptible to Fig.…”
Section: Pre-scan Workup and Patient Preparationmentioning
confidence: 99%
“…Em 2017, Marc J. Gollub, et al avaliaram a acurácia da injeção do meio de contraste na identificação de resposta patológica completa nos pacientes com câncer de reto que foram submetidos terapia adjuvante. Concluíram que um dos parâmetros baseados no realce por contraste dinâmico na RM, o Ktrans, não é capaz de diferenciar pacientes que tiveram ou não resposta completa, mas pode diferenciar aqueles que tiveram resposta de 90% ou mais daqueles que não tiveram essa percentagem de resposta, ressaltando assim o papel promissor da injeção do meio de contraste nesses casos (Gollub e al., 2017).…”
Section: Resultsunclassified
“…Em maio de 2018, a revista Radiologia Abdominal publicou as recomendações da Sociedade de Radiologia Abdominal (SAR) acerca do mesmo tema. Essas recomendações foram elaboradas com base no questionário semelhante ao utilizado pela ESGAR em 2012, com algumas adaptações, que foi então aplicado a especialistas norte-americanos(Gollub e al., 2018). Essas recomendações sugerem: uso de RM de no mínimo 1,5T (não há consenso sobre se o ideal seria a utilização de 1,5T ou 3,0T, uma vez que a sequência de difusão tem sido cada vez mais recomendada e que os artefatos de susceptibilidade são mais prevalentes em aparelhos 3,0 T);  uso de bobina de superfície em todos os casos; um protocolo de rotina deveria incluir/considerar no mínimo:Tabela 5.…”
unclassified
See 1 more Smart Citation